Adsorption, wetting, foaming, and emulsification properties of mixtures of nonylphenol dodecyl sulfonate based on linear alpha-olefin and heavy alkyl benzene sulfonate. Issue 8 (3rd August 2018) - Niu, R. X.; He, J. Y.; Long, B.; Wang, D. Q.; Song, H.; Wang, C.; Qu, G. M.
ABSTRACT: Nonylphenol dodecyl sulfonate (C12 NPAS) has been synthesized, and mixed with heavy alkyl benzene sulfonates (HABS) in different proportions. The effects of different mixing ratios on properties such as adsorption, wetting, foaming, and emulsification, of the C12 NPAS/HABS surfactant mixtures have been systematically investigated. Experimental results have shown that, after mixing, the wetting and foaming properties of C12 NPAS/HABS are improved remarkably. Compared with C12 NPAS and HABS alone, the adsorption and emulsifying properties of C12 NPAS/HABS are far superior, which we attribute to a synergistic effect between these surfactants. GRAPHICAL ABSTRACT: